Mechanochemical Friedel–Crafts Alkylation—A Sustainable Pathway Towards Porous Organic Polymers. Issue 24 (10th May 2017) - Troschke, Erik; Grätz, Sven; Lübken, Tilo; Borchardt, Lars
Abstract: This study elucidates an innovative mechanochemical approach applying Friedel–Crafts alkylation to synthesize porous covalent triazine frameworks (CTFs). Herein, we pursue a counterintuitive approach by utilizing a rather destructive method to synthesize well‐defined materials with intrinsic porosity. Investigating a model system including carbazole as monomer and cyanuric chloride as triazine node, ball milling is shown to successfully yield porous polymers almost quantitatively. We verified the successful structure formation by an in‐depth investigation applying XPS, solid‐state NMR and FT‐IR spectroscopy. An in situ study of pressure and temperature developments inside the milling chamber in combination with two‐dimensional liquid‐state NMR spectroscopy reveals insights into the polymerization mechanism. The versatility of this mechanochemical approach is showcased by application of other monomers with different size and geometry. Abstract : Mechanochemistry meets porosity : Ball milling was applied to synthesize covalent triazine frameworks with permanent porosity. The generality of this approach is showcased by converting various monomers of different size and geometry. The polymerization mechanism is investigated by in situ monitoring of temperature and pressure in the milling chamber as well as NMR spectroscopy.